2013
DOI: 10.1111/iej.12059
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models of pain following root canal treatment: a prospective clinical study

Abstract: Arias A, de la Macorra JC, Hidalgo JJ, Azabal M.Predictive models of pain following root canal treatment: a prospective clinical study. International Endodontic Journal, 46, 784-793, 2013. Aim To determine the probability of the incidence, intensity, duration and triggering of post-endodontic pain, considering factors related to the patient (age, gender, medical evaluation) and to the affected tooth (group, location, number of canals, pulp vitality, preoperative pain, periapical radiolucencies, previous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
187
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(209 citation statements)
references
References 55 publications
14
187
1
7
Order By: Relevance
“…This was relatively similar to the results of postoperative pain after applying five-hundred single-visit root canal treatments, reporting intense in 9.6% of the cases, moderate in 45.8%, and mild in 43.5% [31]. However, in Arias et al's study [31], the cases included single-visit root canal treatments, not retreatments, so it is difficult to compare their results with those of our study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This was relatively similar to the results of postoperative pain after applying five-hundred single-visit root canal treatments, reporting intense in 9.6% of the cases, moderate in 45.8%, and mild in 43.5% [31]. However, in Arias et al's study [31], the cases included single-visit root canal treatments, not retreatments, so it is difficult to compare their results with those of our study.…”
Section: Discussionsupporting
confidence: 84%
“…This was relatively similar to the results of postoperative pain after applying five-hundred single-visit root canal treatments, reporting intense in 9.6% of the cases, moderate in 45.8%, and mild in 43.5% [31]. However, in Arias et al's study [31], the cases included single-visit root canal treatments, not retreatments, so it is difficult to compare their results with those of our study. In contrast, Yoldas et al [3] investigated two-hundred and eighteen single-visit and multiple-visit retreatment cases and reported "none pain" in 73.9%, mild pain in 17.8%, moderate pain in 2.7%, and severe pain in 5.4% of the single-visit asymptomatic group.…”
Section: Discussionsupporting
confidence: 84%
“…The occurrence of postoperative pain of mild intensity is not an occasional event even when endodontic treatment has followed suitable standards [3]. This usually involves acute pain, meaning the correct treatment can be rapidly applied.…”
mentioning
confidence: 99%
“…Post-endodontic pain, especially after primary endodontic therapy, should ideally be eliminated by the treatment; however, analgesics are frequently required to reduce pain [2]. There is a solid association among pulp status and postoperative pain, influencing the capability of pain, which may undermine the patient's confidence in the procedure and the clinician [3]. Ketorolac is an excellent acting analgesic used widely in surgery and medicine [22].…”
mentioning
confidence: 99%
“…Extrusion of microorganisms or debris during endodontic treatment results in inflammatory response (1)(2)(3)(4). A recent systematic review showed that between 3% and 58% of patients were reported to have experienced endodontic postoperative pain (5).…”
Section: Introductionmentioning
confidence: 99%